Teaching Patient Safety in the Undergraduate Curriculum-What Students Think - Ramachandran, G; Aung, KKM (RA Journal Of Applied Research, 2023)
Patient Safety was incorporated into the undergraduate curriculum in our faculty in 2015. The faculty developed an introductory curriculum based on the WHO Patient Safety Manual. Students were then required to identify and work on a patient safety project during their clinical rotations. All reports were graded and completion was a requirement for the final professional examinations. Students’ impressions on the teaching programme and understanding of patient safety was gauged with a questionnaire. The programme improved awareness of students in the area. Ideal teaching and assessment mechanisms need to be developed to improve and sustain outcomes.